Electrocardiographic findings and QT dispersion in children with chest pain - (:unkn) unknown (GALENOS YAYINCILIK, 2009)
Aim: Chest pain is common in childhood and the reason can not be found in most cases. Its known relation with coronary artery disease in adult patients causes anxiety in patients and parents. QT dispersion is studied in this group of patients and risk of sudden death and life threatening arrhythmia is investigated. Material and Method: The study group consisted of 10 girls and 13 boys aged between 5 and 15 years and the control group consisted of 21 boys and 7 girls aged between 5.5 and 15 years. Heart rate, RR interval, RR variability, PR interval, time and amplitude of P wave, P wave axis, QRS distance, QRS axis, QT interval, corrected QT (QTc), QT dispersion and QTc dispersion obtained from the surface electrocardiograms were compared. Results: A significant difference was not found between the groups regarding heart rate, RR interval, RR variability, PR interval, P wave and QRS axis, QRS interval and QT interval. P wave amplitude was higher in the patients with chest pain than the control group (1.6 +/- 0.6 and 1.3 +/- 0.04 respectively, p<0.03). QT dispersion in the patients and the controls were 65 +/- 23 msn and 61 +/- 17 msn. QTc dispersion in the patients and in the controls were 106 +/- 2 msn and 113 +/- 23 msn. QT dispersion values using 12 derivation electrocardiograms, precordial derivations and extremity derivations were correlated to each other (r=0.47, p<0.005 and r=0.24, p<0.02). Conclusions: Children with idiopathic chest pain do not have an increased risk for life threatening arrhythmia or sudden death. Increased P wave amplitude suggests the need of evaluation for pulmonary dysfunction. (Turk Arch Ped 2009; 44: 53-6)
Keywords: Arrhythmia; chest pain; electrocardiography; QT dispersion; MITRAL-VALVE PROLAPSE; VENTRICULAR ARRHYTHMIAS; INTERVAL DISPERSION; HYPERTROPHIC CARDIOMYOPATHY